Analysis Of Intelligibility And Connectivity-Integration Relationships In The Canggu Village Space Network Based On Space Syntax - Prabawa, Made Suryanatha; Widanan, I Wayan; Wiguna, Made Mas Surya; Dwi Putra, Made Jaguandana; Antara, I Made Rudita (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Canggu Village, located in Badung Regency, Bali, is a popular tourist destination known for its beach and nightlife, which has led to rapid tourism development. This growth has both positive and negative impacts, including traffic congestion and uncontrolled construction. To address these issues, this study analyzes the spatial planning of Canggu Village, focusing on accessibility, connectivity, interaction, and intelligibility. The aim of this analysis is to be able to produce output values ​​for aspects of the level of effectiveness of spatial planning which in the future can be used as a reference for providing recommendations for more appropriate village tourism development so that tourism development and community residential needs can still stand side by side. Using a quantitative-experimental approach and Space Syntax analysis via the DepthmapX application, the research finds: (a) low to moderate local connectivity (average 2.46) with limited intersections; (b) relatively low local integration (mean 1.04), requiring more effort for movement; (c) high intelligibility (R² = 0.87722), allowing effective navigation; and (d) numerous minor roads emerging from major routes, creating an accessible spatial structure. This raises questions about the factors influencing connectivity amid unplanned development. Suggested development plan according to research results are: 1) Improving Connectivity in Local Areas (intersection/direct routes); 2) Boosting Integration Between Tourism Zones; 3) Optimizing navigation; 4) Tourism Supporting Infrastructure Development; 5) Involvement of Technology and Smart Tourism.